2023
DOI: 10.7554/elife.81184
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the fatty acid binding proteins disrupts multiple myeloma cell cycle progression and MYC signaling

Abstract: Multiple myeloma is an incurable plasma cell malignancy with only a 53% 5-year survival rate. There is a critical need to find new multiple myeloma vulnerabilities and therapeutic avenues. Herein, we identified and explored a novel multiple myeloma target: the fatty acid binding protein (FABP) family. In our work, myeloma cells were treated with FABP inhibitors (BMS3094013 and SBFI-26) and examined in vivo and in vitro for cell cycle state, proliferation, apoptosis, mitochondrial membrane potential, cellular m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Cell Lines and Culture Conditions MM.1S (ATCC), RPMI-8226 (ATCC), and OPM-2 (DSMZ) cells, as well as luciferase-and gfpexpressing MM.1S (MM.1S gfp+/luc+ ) and MM.1R (MM.1R gfp+/luc ) cell lines were obtained and cultured as previously described (7) in RPMI-1640 basal media supplemented with 10% (15% for U266B1 cells) fetal bovine serum (FBS, VWR) with 1% antibiotic-antimycotic (ThermoFisher Scientific, Cat # 15240112) at a cell density of 4.166x10 5 cells/mL in tissue culture-treated T-75 flasks (VWR) (7). MM.1S gfp+/luc+ cells were used for experiments involving MM.1S cells unless otherwise stated.…”
Section: Cancer Dependency Map Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Cell Lines and Culture Conditions MM.1S (ATCC), RPMI-8226 (ATCC), and OPM-2 (DSMZ) cells, as well as luciferase-and gfpexpressing MM.1S (MM.1S gfp+/luc+ ) and MM.1R (MM.1R gfp+/luc ) cell lines were obtained and cultured as previously described (7) in RPMI-1640 basal media supplemented with 10% (15% for U266B1 cells) fetal bovine serum (FBS, VWR) with 1% antibiotic-antimycotic (ThermoFisher Scientific, Cat # 15240112) at a cell density of 4.166x10 5 cells/mL in tissue culture-treated T-75 flasks (VWR) (7). MM.1S gfp+/luc+ cells were used for experiments involving MM.1S cells unless otherwise stated.…”
Section: Cancer Dependency Map Analysismentioning
confidence: 99%
“…XFe96 analyzer (Agilent Technologies), as previously described (7). Cells were also analyzed for total, mitochondrial, and glycolytic ATP production rates using a Seahorse XF ATP Production Rate Assay according to the manufacturer's instructions.…”
Section: Mitochondrial Function Was Determined Using a Mitochondrial ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated that SBFI26 elicits intracellular apoptotic signals and induces apoptosis in PC3M cells by regulating the FABP5‐VEGF‐PPAR axis 10,23 . While previous studies have shown that SBFI26 can impede the proliferation of TNBC cells, its inhibitory effects on breast cancer have not yet been reported 47 …”
Section: Introductionmentioning
confidence: 98%
“…10,23 While previous studies have shown that SBFI26 can impede the proliferation of TNBC cells, its inhibitory effects on breast cancer have not yet been reported. 47 In this study, we investigated the impact of SBFI26 on breast cancer cell proliferation and analysed the transcriptome data following treatment with SBFI26 in TNBC cells. Through KEGG and GO analysis of transcriptomic data, it was observed that SBFI26 treatment up-regulated the expression of ferroptosis-related genes in TNBC cells compared to the control group.…”
mentioning
confidence: 99%